Links and tensions between disability and mental health - Arantes, Ricardo Lugon; Palombini, Analice de Lima (Argumentum, 2024)
There is a gap between policies and struggles related to the field of Mental Health and that of Persons with Disabilities. This article discusses the connections and tensions between these fields using Mental Health Studies and Disability Studies sources. Based on eleven interviews with Brazilian activists, researchers, and managers, we discuss the translation and choice of terms employed in Brazil and the legal frameworks surrounding these policies. In the Global South, there is little academic output, with an emerging movement in Africa, while in India the feminist struggle is allied to confronting the patriarchal oppressions reproduced by Psychiatry. There is synergy between the struggles and convergence around access to the right to income linked to disability, but there are divergences in the choice of the terms with which these collectives designate themselves.